Neuropathophysiology, Genetic Profile, and Clinical Manifestation of Mucolipidosis IV—A Review and Case Series - Jezela-Stanek, Aleksandra (Int J Mol Sci, 2020)
Mucolipidosis type IV (MLIV) is an ultra-rare lysosomal storage disorder caused by biallelic mutations in MCOLN1 gene encoding the transient receptor potential channel mucolipin-1. So far, 35 pathogenic or likely pathogenic MLIV-related variants have been described. Clinical manifestations include severe intellectual disability, speech deficit, progressive visual impairment leading to blindness, and myopathy. The severity of the condition may vary, including less severe psychomotor delay and/or ocular findings. As no striking recognizable facial dysmorphism, skeletal anomalies, organomegaly, or lysosomal enzyme abnormalities in serum are common features of MLIV, the clinical diagnosis may be significantly improved because of characteristic ophthalmological anomalies. This review aims to outline the pathophysiology and genetic defects of this condition with a focus on the genotype–phenotype correlation amongst cases published in the literature. The authors will present their own clinical observations and long-term outcomes in adult MLIV cases.